Molecular dynamic investigation on sulfur migration during hydrogen production by benzothiophene gasification in supercritical water. (5th August 2021) - Liu, Shanke; Jin, Hui; Yang, Yan; Yu, Lijun
Abstract: Benzothiophene (BT) is a key sulfur-containing intermediate product in the thermal conversion process of coal and heavy oil. The migration process of the sulfur element may affect the thermal utilization design of BT. In this paper, BT was used as a model compound to simulate the supercritical water gasification (SCWG) process by molecular dynamics with a reactive force field (ReaxFF) method, and the laws of hydrogen production and sulfur migration mechanisms were obtained. Increasing the molecule number of supercritical water (SCW) and increasing the reaction temperature can enhance the generation of hydrogen and promote the conversion of organic sulfur to inorganic sulfur. Water was the main source of H2, and H2 S was the main gaseous sulfur-containing product. SCW had a certain degree of oxidation due to a large number of hydroxyl radicals, which could increase the valence of sulfur. The conversion process of BT in SCW was mainly divided into four stages, including thiophene ring-opening; sulfur separation or carbon chain broke with sulfur retention; carbon chain cleaved, and gas generation. The lumped kinetic parameters of the conversion of sulfur in BT to inorganic sulfur were calculated, and the activation energy was 369.98 kJ/mol, which was much lower than those under pyrolysis conditions. This article aims to clarify the synergistic characteristics of hydrogen production and sulfur migration in the SCWG process of BT from the molecular perspective, which is expected to provide a theoretical basis for pollutant directional removal during hydrogen production by sulfur-containing organic matters in SCW. Highlights: Molecular dynamic investigation for hydrogen production by SCWG of benzothiophene was carried out by ReaxFF method. More supercritical water molecules and higher temperature could enhance the generation of hydrogen and inorganic sulfur. Hydroxyl radicals in SCW had oxidation and could increase the valence of sulfur. Pathway of benzothiophene gasification in SCW was proposed and lumping kinetic parameters were calculated.